Molecular Tension Probes to Investigate the Mechanopharmacology of Single Cells: A Step Towards Personalized Mechano-medicine - Galior, Kornelia (Adv Healthc Mater, 2018)
Given that dysregulation of mechanics contributes to diseases ranging from cancer metastasis to lung disease, it is important to develop methods for screening the efficacy of drugs that target cellular forces. Here, we use nanoparticle-based tension sensors to quantify the mechanical response of individual cells upon drug treatment. As a proof-of-concept, the activity of bronchodilators is tested on human airway smooth muscle cells derived from seven donors, four of which are asthmatic. It is revealed that airway smooth muscle cells isolated from asthmatic donors exhibit greater traction forces compared to the control donors. Additionally, the mechanical signal is abolished using myosin inhibitors or further enhanced in the presence of inflammatory inducers, such as nicotine. Using the signal generated by the probes, single-cell dose-response measurements are performed to determine the “mechano” effective concentration (mechano-EC(50)) of albuterol, a bronchodilator, which reduces integrin forces by 50%. Mechano-EC(50) values for each donor presented discrete readings that were differentially enhanced as a function of nicotine treatment. Importantly, donor mechano-EC(50) values varied by orders of magnitude, suggesting significant variability in their sensitivity to nicotine and albuterol treatment. To the best of our knowledge, this is the first study harnessing a piconewton tension sensor platform for mechanopharmacology.